Optimalisasi Pemetaan Digital untuk Peningkatan Aksesibilitas UMKM melalui Google Maps - Cinta Aisyahtul Kubra; Intan Alisa; Muhammad Sudepman Rohim Tarigan; Siti Aisyah (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to analyze the role of digital mapping, particularly through Google Maps, in enhancing accessibility and competitiveness of Micro, Small, and Medium Enterprises (MSMEs). Digital mapping allows MSMEs to display business locations, operating hours, product photos, and contact information, facilitating consumers in finding their services. Integration with review and rating features also increases consumer trust and strengthens the professional image of the business. The study uses a qualitative descriptive approach through literature review on MSME digitalization, digital marketing strategies, and Google Maps implementation. The findings indicate that optimal utilization of digital mapping positively impacts business visibility, expands market reach, and fosters two-way interaction between business owners and consumers. Challenges such as limited digital literacy and funding can be addressed through training programs, mentorship, and government support. Therefore, optimizing digital mapping via Google Maps can serve as a crucial strategy for sustainable MSME development, helping businesses adapt to market trends and contribute significantly to national economic growth.